(untitled) (Revista Electrónica REDINE, 2025)
The activities of educational institutions are of fundamental importance for the comprehensive education of children and adolescents entrusted to them by society. This aspect is closely related to the availability of resources, although it is especially critical with regard to the planning and organization of educational processes, as well as their execution by management staff. In this sense, organizational learning is considered a key element to ensure optimal performance, in efficiency and effectiveness, increasing the capacity to face future challenges. Likewise, it is essential that this professional has the appropriate personal characteristics, experience and leadership that promotes the achievement of educational objectives. Therefore, this research aims to promote the role of the teacher-manager from a decolonizing approach in Primary Education, Los Guayos municipality, Carabobo state. It is framed within the socio-critical paradigm, a participatory action research methodology, a line of curricular management research, using participatory observation and in-depth interview techniques, a guiding instrument of structured questions. The key informants were a supervisor, two directors, two teachers, a pedagogical coordinator and a community council. For the analysis of the information, triangulation and categorization techniques were applied. The results show that, if the importance of a management that motivates and encourages other ways of seeing education is not managed, the school will simply continue to educate a group of students alone, where their learning will not be in line with what is demanded by the community and the family. Among the conclusions are that: Adopt a new management paradigm. The convergence of these elements demonstrates that decolonization is not merely a theory, but a tangible practice that demands transformative teacher leadership capable of reinterpreting the curriculum and school dynamics.